Analisis pengaruh herding behavior dalam memoderasi keputusan investasi saham pada Mahasiswa UPN Veteran Jawa Timur - Mumtazah, Muhammad Rizqi; Anwar, Muhadjir (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The effect of herding behavior in moderating stock investment decisions on UPN Veteran East Java students by using financial literacy and risk tolerance as moderating variables is the aim of this study. By using quantitative methods on students who are members of the IDX Gallery UPN Veterans East Java with a total of 80 students along with decision-making techniques using saturated samples. Partial Least Square technique as a data analysis tool. In this study, researchers used questionnaires to obtain primary data. The results showed that financial literacy had an effect, risk tolerance had no effect on stock investment decisions, and herding behavior significantly moderated financial literacy (X1) and risk tolerance (X2) on stock investment decisions.